PHENOTYPING OF NILEM (Osteochilus hasselti) MANGUT STRAIN CULTIVATED IN CENTRAL AND WEST JAVA - Pramono, Taufik Budhi; Kusnendar, Rinaldi; Wijaya, Rudy; Nugrayani, Dewi; Marnani, Sri (Jurnal Perikanan Unram, 2024)
Phenotypic characters are one of bases for conducting selective breeding. The phenotypic characters of Nilem Mangut strains cultivated in several region can provide basic information for the development of its cultivation. This study aims was to determine the comparison of the characteristics of the quantitative phenotype with the meristic morphometric and growth pattern of Nilem (Osteochilus hasseltii) Mangut strains cultivated in different regions. This research was conducted using active survey methods in the field and laboratory. 90 fish were taken randomly from 3 different locations, namely Banyumas, Purbalingga and Tasikmalaya, samples were taken 30 fish/location. The results showed that the morphometric diversity coefficient of Mangut Nilem ranged from 4.93-17.99% (Banyumas), 10.35-21.41% (Purbalingga) and 9.11-24.12% (Tasikmalaya) while the coefficient The meristic diversity of Mangut Nilem Fish ranged from 6.89-13.02% (Banyumas), 6.05-9.32% (Purbalingga) and 5.78-10.78% (Tasikmalaya). Morphometric and meristic characters of Mangut Nilem Fish from several locations have positive correlation (have unidirectional relationships between characters) and negative (have opposite relationships between characters). Based on the relationship between length and weight, the Mangut Nilem fish in Banyumas, Purbalingga and Tasikmalaya had a b value respectively, namely 6,0222, 5,42 and 3,39 showing a positive allometric growth pattern (weight gain is more dominant than length gain). The condition factor for Mangut Nilem fish has a value range of 1.32-1.34. Tasikmalaya has the best fish farming pattern.